Minimum Wage: Slovenia from the Perspective of the European Union - Laporšek, Suzana (Naše gospodarstvo/Our economy, 2013)
The aim of this paper is to present the purpose and objectives of the minimum wage, putting the Slovenian minimum wage into the context of the European Union. Every EU member state has one form of the minimum wage regulation. In most countries, including Slovenia, minimum wage is set at the national level by law or national co- llective agreement, meaning that all workers are eligible for the minimum wage. Re- garding the ratio between minimum and average wage, Slovenia ranks among countries with the highest minimum wage. According to the numerous empirical studies, Slovenia’s relatively high minimum wage might have adverse effects on the labour market outcomes, especially for vulnerable groups in the labour market, as well as productivity.